DASAR PENGENAAN PAJAK ATAS OBJEK PAJAK YANG MENGHASILKAN EMISI GAS RUMAH KACA: STUDI KEBIJAKAN NILAI EKONOMI KARBON - Nadia Wulandari Rotty, (2023)
The objective of this research is to grasp about the implementation of the Carbon Pricing policy in Indonesia and to investigate the reasons for the postponement of the imposition of carbon taxes in the coal-fired power plant (PLTU) sector, which was originally scheduled to commence in 2022. This study utilized a normative juridical research approach with an invitation, comparison, and conceptual approach. The data in this study is secondary data obtained through library research from primary, secondary, and tertiary legal materials. The data analysis technique used in this study was qualitative, with the research results being explanatory and exploratory. This research also finds problems with the low minimum carbon tax rate applied and the potential limited expansion of the carbon tax sector in Indonesia towards the energy industry sector and the transportation sector. Therefore, for the successful implementation of carbon taxes in Indonesia in 2025, it is necessary to issue regulations for the implementation of carbon tax collection as well as carbon tax roadmaps by the government. The government also needs to recalculate carbon tax rates to adjust to the national greenhouse gas emission reduction target in 2030.